10.25047 Formulasi Soft Cookies Berbasis Tepung Kacang Hijau dan Tepung Kacang Tanah Sebagai Makanan Selingan Sumber Protein pada Wanita Usia Subur: - - Harumi, Rahmatika; Fitriyah, Dina; Oktafa, Huda; Warsito, Heri (Politeknik Negeri Jember, 2025)
Protein is a crucial nutrient necessary for the body to perform various vital functions support growth, repair tissues, and maintain reproductive health, especially for women of reproductive age. Adequate protein intake helps prevent chronic energy deficiency (CED) and stunting. This study aimed to develop soft cookies produced with mung bean flour and peanut flour as a protein-rich snack. The research applied a Completely Randomized Design (CRD) with five formulations of mung bean flour and peanut flour ratios: (90%:10%), (80%:20%), (70%:30%), (60%:40%), and (50%:50%). The analysis covered protein content, organoleptic properties (color, taste, aroma, texture), nutritional composition, and the best formulation. The best result was obtained from formulation P5, which contained 6,28% moisture, 1.49% ash, 14,77 g protein, 23,28 g fat, 54,19 g carbohydrates, and 486 kcal per ,00 grams. This formulation was preferred by panelists due to its brown color, sweet taste, neutral mung bean aroma, and soft texture. A 60 g serving provides 294 kcal, 9 g protein, 13.96 g fat, and 33 g carbohydrates. These soft cookies have the potential to be a nutritious, affordable, plant-based protein snack that supports the prevention of CED and stunting. Keywords: Soft cookies, snack, mung bean flour, peanut flour, CED